Analisis Desain Kubikel 20kV untuk Peningkatan Efisiensi dan Keandalan Sistem Distribusi Listrik - Muhamad Sadewa; Endi Permata (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Electrical energy is a vital element in daily life, supporting nearly all equipment used. One of the main components in the electrical distribution system is the 20 kV cubicle. This cubicle plays an essential role in controlling power flow, protecting the system from faults, measuring electrical parameters, and enabling remote monitoring and control. Additionally, the cubicle functions to maintain the stability, reliability, and efficiency of power flow to load centers. However, various technical issues, such as short-circuit faults, protection system failures, and corona phenomena caused by high humidity, often threaten its performance. This study aims to evaluate and optimize the design and operation of 20 kV cubicles in electrical distribution systems. The research focuses on analyzing technical factors that affect energy efficiency and system reliability, as well as identifying challenges in implementation, such as installation and maintenance issues. The research methods include literature reviews, interviews, and field observations. The results indicate that modular designs, high-quality insulating materials, and modern technologies such as Intelligent Electronic Devices (IEDs) and Supervisory Control and Data Acquisition (SCADA) enhance system efficiency and reliability. It is recommended that cubicle designs be adapted to the load capacity and routine maintenance be performed to maintain efficiency and extend equipment lifespan.